Clinical Results According to Inferior Oblique Manipulation in Patients with Inferomedial Blowout Fracture Involving the Orbital Strut - Park J; Jo S; Choi HY (Clinical Ophthalmology, 2022)
Jungyul Park,1,2 Sunghyun Jo,1 Hee-Young Choi1,2 1Department of Ophthalmology, School of Medicine, Pusan National University Hospital, Busan, South Korea; 2Biomedical Research Institute, Pusan National University, Busan, South KoreaCorrespondence: Hee-Young Choi, Department of Ophthalmology, School of Medicine, Biomedical Research Institute, Pusan National University, 179 Gudeok-Ro, Seo-Gu, Busan, 49241, Republic of Korea, Tel +82-51-240-7324, Fax +82-51-242-7341, Email hychoi@pusan.ac.krBackground: Detachment of the inferior oblique muscle may be necessary under certain circumstances to repair a large inferomedial orbital fracture involving the orbital strut. This study aimed to evaluate the outcomes of patients who underwent surgeries with and without inferior oblique muscle reattachment after its detachment to repair the orbital wall fractures.Methods: Forty patients who underwent repair of combined floor and medial orbital wall fracture involving the orbital strut at a single tertiary institution between January 2014 and December 2020 were reviewed. Groups 1 and 2 comprised 20 patients each, who underwent surgery with inferior oblique muscle detachment without and with reattachment, respectively, and were followed up for at least 6 months postoperatively. Enophthalmos, Goldmann diplopia test, alignment test, ocular motility test, and orbital inferomedial angle ratio were the outcome measures.Results: Statistically significant improvement was observed in ocular motility, diplopia, and enophthalmos postoperatively at the 1- and 6-month follow-up (p < 0.01). The mean postoperative inferomedial angle ratio (102.28 ± 10.62%) was improved significantly compared with the preoperative inferomedial angle ratio (115.61 ± 4.38%) (p = 0.004) in all patients. After surgery, inferior oblique muscle underaction was observed in seven and six patients in groups 1 and 2, respectively, which was associated with preoperative extraocular movement limitation and strabismus. Two patients showed diplopia in both groups at the last follow-up; they had inferior oblique muscle underaction but no enophthalmos.Conclusion: Orbital fracture repair with or without inferior oblique muscle reattachment was clinically effective and safe; however, patients with preoperative strabismus and extraocular motility limitation should be informed of the increased risk of postoperative complications.Keywords: orbital fracture, inferior oblique muscle, diplopia, strabismus, post-operative complications